Tools for visualization of phosphoinositides in the cell nucleus - Kalasova, Ilona; Fáberová, Veronika; Kalendová, Alžběta; Yildirim, Sukriye; Uličná, Lívia; Venit, Tomáš; Hozák, Pavel (Histochemistry and cell biology, 2016)
Phosphoinositides (PIs) are glycerol-based phospholipids containing hydrophilic inositol ring. The inositol ring is mono-, bis-, or tris-phosphorylated yielding seven PIs members. Ample evidence shows that PIs localize both to the cytoplasm and to the nucleus. However, tools for direct visualization of nuclear PIs are limited and many studies thus employ indirect approaches, such as staining of their metabolic enzymes. Since localization and mobility of PIs differ from their metabolic enzymes, these approaches may result in incomplete data. In this paper, we tested commercially available PIs antibodies by light microscopy on fixed cells, tested their specificity using protein-lipid overlay assay and blocking assay, and compared their staining patterns. Additionally, we prepared recombinant PIs-binding domains and tested them on both fixed and live cells by light microscopy. The results provide a useful overview of usability of the tools tested and stress that the selection of adequate tools is critical. Knowing the localization of individual PIs in various functional compartments should enable us to better understand the roles of PIs in the cell nucleus.
Keywords: Fluorescent Antibody Technique, Indirect; fluorescenční protilátková technika nepřímá; kultivované buňky; PI(4,5)P2; fluorescenční mikroskopie; Antibodies; protilátky; Microscopy, Fluorescence; Antigen-Antibody Reactions; Phosphoinositides; Microscopy, Confocal; buněčné jadérko; konfokální mikroskopie; Cells, Cultured; PI(4)P; Humans; fosfatidylinositoly; reakce antigenu s protilátkou; Cell Nucleolus; Phosphatidylinositols; lidé; Nucleus